Harmonizing Imagination and Technology: Emmas Fröhlicher Tag-A Fusion of Printed Picture German Storybook and Digital Web Experience on Google Sites - Pratama, Kisma Bagus; Aini, Desti Nur; Yusuf, Robe'ah (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
This study aims to develop a hybrid educational tool, combining a printed picture German storybook with a digital web experience, to assess the effectiveness of the hybrid tool in enhancing German language learning for beginners, specifically focusing on language acquisition and imaginative skills. This research adopts the Research and Development (R&D) approach, employing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The study involves the creation of "Emmas Fröhlicher Tag," starting with the analysis of educational needs, design and development of content, implementation in an educational setting, and finally, evaluation of its effectiveness through qualitative measures. The fusion of traditional and digital learning tools in "Emmas Fröhlicher Tag" demonstrates the potential to harmonize imagination and technology for German learners. The integration of printed and digital elements provides a holistic learning experience, catering to diverse learning styles and enhancing language acquisition and imaginative skills. Further research can explore the scalability and adaptability of this hybrid model across different cultural and linguistic contexts. Additionally, continuous updates and improvements to the digital component can ensure the tool remains relevant and engaging for evolving educational needs.